Effect of particle size on production of citric acid from oil palm empty fruit bunches as new substrate by wild Aspergillus niger - Bari, M.N.; Alam, Md. Zahangir; Muyibi, Suleyman Ayemu; Jamal, Parveen; Al-Mamun, Abdullah (Asian Network for Scientific Information, 2010)

(untitled)
An investigation was carried out to evaluate the effect of different particle size of oil palm Empty Fruit Bunches (EFB) and their distribution as new substrate for the production of citric acid through Solid State Bioconversion (SSB) in laboratory scale by Aspergillus niger. The experiment was carried out to observe the productivity of citric acid with different particle size of EFB in 250 mL Erlenmeyer flasks. The result obtained through this study showed that the 0.5 mm down graded particle of EFB gave the highest production of citric acid compared to other particle size. The maximum production of citric acid of 131.3 g kg-1-EFB with the production rate of 16.4 g kg-1-day was obtained from EFB with particle size of 0.5 mm after 8 days of bioconversion. Furthermore, the results of particle size distribution show that the well-graded particle size of EFB produced the highest citric acid compared to uniformly-graded and gap-graded particle.